2020
DOI: 10.1210/endocr/bqaa015
|View full text |Cite
|
Sign up to set email alerts
|

Androgens Increase Accumulation of Advanced Glycation End Products in Granulosa Cells by Activating ER Stress in PCOS

Abstract: Polycystic ovary syndrome (PCOS) is associated with hyperandrogenism, and we previously found that androgens activate endoplasmic reticulum (ER) stress in granulosa cells from patients with PCOS. In addition, recent studies demonstrated the accumulation of advanced glycation end products (AGEs) in granulosa cells from PCOS patients, which contribute to the pathology. Therefore, we hypothesized that androgens upregulate the receptor for AGEs (RAGE) expression in granulosa cells by activating ER stress, thereby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 61 publications
0
37
0
Order By: Relevance
“…Additionally, overexpression of key autophagy regulatory protein mechanistic target of rapamycin kinase (mTOR) can lead to insulin resistance during the pathological development of PCOS (Liu et al 2018;Song et al 2018). Besides, mitochondrial dysfunction and ER stress have been shown to participate in the pathogenesis of PCOS (Azhary et al 2020;Zeng et al 2020). Previous studies suggested that autophagy was closely related to mitochondrial dysfunction (Go et al 2015) and ER stress (Lee et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, overexpression of key autophagy regulatory protein mechanistic target of rapamycin kinase (mTOR) can lead to insulin resistance during the pathological development of PCOS (Liu et al 2018;Song et al 2018). Besides, mitochondrial dysfunction and ER stress have been shown to participate in the pathogenesis of PCOS (Azhary et al 2020;Zeng et al 2020). Previous studies suggested that autophagy was closely related to mitochondrial dysfunction (Go et al 2015) and ER stress (Lee et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with PCOS, advanced glycation endproduct (AGE) levels were significantly increased compared with those in matched normal-weight controls [53,54]. AGEs can alter insulin receptor substrate and AKT phosphorylation, thereby stimulating the downstream PI3K signaling cascade and compromising the effects of insulin signaling [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…28-day old C57BL/6J female mice were purchased from Wenzhou medical University and divided into three groups: control, dehydroepiandrosterone (DHEA)-induced PCOS, and DHEA+flutamide (Flut, an AR antagonist). PCOS mouse model was created by the administration of DHEA as described previously ( 22 , 23 ). Briefly, control mice were subcutaneously injected with sesame oil and, and implanted subcutaneously with an empty pellet; PCOS mice were subcutaneously injected with DHEA (Sigma-Aldrich) and implanted subcutaneously with an empty pellet; DHEA+Flut mice were subcutaneously injected with sesame oil and implanted subcutaneously with a pellet containing 20 mg flutamide (Innovative Research of America, Sarasota, FL, USA).…”
Section: Methodsmentioning
confidence: 99%